Analisis HOTS Siswa pada Materi Pola Bilangan menggunakan Pendekatan PMRI melalui Sistem LSLC - Kustanti Situmorang; Ratu Ilma Indra Putri; Candra Koni Lelyana (Universitas Hamzanwadi, 2020)
This research aims to determine the student’s higher order thinking skill (HOTS) after learning using the PMRI through LSLC is done approach to the material of number patterns in class VIII. This type of research is descriptive. The subjects of this study were students of class VIII.5 Junior High School number 18 Palembang amounting to 31 students. Data collectin techniques used were observations, giving test questions amounted to one questons in the form of descriptions, and interviews. After conducting the research, there have been many indicators of higher order thinking skills raised by students even though there are still some students who don’t bring up indicators. In addition, by using the PMRI approach and the LSLC system, students become mutually learning and active in learning. The conclusion of this research is the ability of HOTS students in class VIII.5 is enough, which can be seen from the scores obtained by students in the test questions that are in the range of grades 41-60. In addition, the emergence of the analysis (C4) indicator most often appears as much as 63.33%, evaluation (C5) as much as 30% and the creation (C6) indicator is the least indicator that appears as much as 20%.